'The Natives Freely Spoke of the Custom': Sex-Selective Infanticide and Māori Depopulation, 1815–58. Issue 1 (2nd January 2021) - Chapple, Simon
ABSTRACT: Was sex-selective infanticide of girls prevalent amongst Māori in the first half of the 19th century? If so, why? Why might the practice have evolved and why did it disappear? What impact did it have on depopulation? A body of contemporary evidence by reliable observers suggests considerable sex-selective infanticide. Recorded motivations for female infanticide relate primarily to warfare, although other reasons are also advanced. Contemporary census data showing unbalanced Māori sex ratios to the detriment of females, especially children, provide corroborative quantitative evidence. Sex-selective infanticide probably arose concomitantly with war and resource pressures in the mid 16th century. While it contributed significantly to overall Māori death rates, there is no empirical evidence suggesting a musket-war related rise in sex-selective infanticide. Thus, it made no causal contribution to post-contact depopulation. However, its elimination from the mid-1830s contributed to ending depopulation by the 1890s.